O desenvolvimento profissional de professores de educação física e a formação continuada: repercussões do mestrado acadêmico - Clates, Daniela de Moura (2019)
This research is in Sociocultural and Pedagogical Studies Concentration Area, specifically in Physical Education Theoretical-Pedagogical Studies Research Line of the Post-graduation Program on Physical Education of the Federal University of Santa Maria (UFSM), Rio Grande do Sul (RS), Brazil. In this research we seek to understand how the Academic Master degree done by Physical Education teachers, of Santa Maria/(RS) Municipal Education System, has an impact on the professional development process of these teachers. By knowing the formative trajectory of eight teachers who collaborate in the study, we aim to: a) identify what are the meanings that these teachers attribute to continuing education; b) identify the relations that teachers establish among the Master elaborated learnings and the school teaching work; c) understand the role of the Master degree in the professional identity (re)building of these teachers and; d) identify the knowledge that teachers recognize as pertinent to their school teaching work. This is a qualitative study conducted through the (auto) biographical method / life stories. Thus, the research followed the ethical guidelines as determined by UFSM Research Ethics Committee, which was approved in March, 2019. The research design allowed us to construct two categories: 1. Drawing trajectories: personal dimensions imbricated in the formative process and 2. Unraveling the continuing formation process, arguing elements that guide us to a theoretical-analytical discussion. The investigative process led us to note that the Academic Master degree reflected in various ways on the collaborators’ professional development, considering the biographies and the trajectory lived by them. The teachers’ diverse sociocorporeal experiences are related to the professional choice and, the different experiences lived during the initial formation have a prominent place in their formative process, engendering important learning for the teaching practice. The process of initiation in teaching and professional development to a large extent seem to have been influenced by the Academic Master degree in different ways. The diversity present in the processes of doing the Academic Master does not prevent that there is a convergence in relation to the recognition of the Master repercussion on the pedagogical practices for some teachers or, on the teachers’ identity considering some of them.